The case for reviewing Malaysian civil servants’ salary - Mohd Adnan, Normala; Aminudin, Rabi'ah; Jamaiudin, Norhaslinda (Stratsea, 2023)
This article explores the Malaysian government’s effort to review the current remuneration system for the public sector in Malaysia as part of the Malaysia Madani reform initiative. This comes at timely manner as the remuneration system for the public sector has to adapt to a challenging economic landscape, volatile political conditions, and rapid technological advancement to ensure an effective and sustainable remuneration system for the public sector.